Visual analytics and interactive technologies : data, text, and web mining applications - Zhang, Qingyu, 1970-; Segall, Richard, 1949-; Cao, Mei, 1969- (Hershey, PA : Information Science Reference, 2011)
'This book is a comprehensive reference on concepts, algorithms, theories, applications, software, and visualization of data mining, text mining, Web mining and computing/supercomputing, covering state-of-the-art of the theory and applications of mining'--
Includes bibliographical references and index.
Keywords: Data mining